Creative Shipwrecks: Coleridge’s The Rime of the Ancient Mariner and Byron’s Don Juan - Baker, L. (Romanticism on the Net, 2007)
AbstractContemporary discussions of English Romantic philosophers and their theories often include such names as William Wordsworth, Samuel Taylor Coleridge, William Hazlitt, Thomas DeQuincey, and Charles Lamb, but rarely do they treat of George Gordon, Lord Byron. While Byron’s reputation was not built upon complex philosophical explications of literary theory, the passion of his life did not preclude that of his mind. He has left us with no overtly philosophical work, and yet, many of the digressions in Don Juan are directed at the poets and philosophers of his time and some others seem to point us to a coherent system of thought about literature and how it works. Specifically, Juan’s voyage at sea contains several passages which parody Coleridge’s Rime of the Ancient Mariner. Some of these similarities have been explored, but are frequently treated as if Byron were simply creating a pastiche of contemporary literature. However, Coleridge had used the Rime to elucidate a portion of his understanding of how literature works. It seems possible that Byron is purposely answering Coleridge in the second canto of Don Juan. Thus, we may be able to use Byron’s natural imagery and poetic technique to piece together a philosophical statement from that most unphilosophical of Romantics, Lord Byron.